Temporal distribution of peak running demands relative to match minutes in elite football - Thoseby, Bradley; Govus, Andrew; Clarke, Anthea; Middleton, Kane; Dascombe, Ben (Biology of Sport, 2022)
The peak match running demands of football (soccer) have been quantified across time durations of 1–10 min, however, little is known as to when the peak match running demands occur within match play. Data were collected from 44 elite footballers, across 68 fixtures (Files = 413, mean ± SD; 11 ± 8 observations per player, range; 1–33), with peak match running demands quantified for each playing half at ten incremental rolling average durations (1 min rolling averages, 2 min rolling averages, etc.). Data were assessed if players completed the full match. Three measures of running performance were assessed total distance (TD), high-speed distance (> 19.8 km·h-1) (HSD) and average acceleration (AveAcc)], with the in-game commencement time of the peak running demands recorded. Descriptive statistics and normality were calculated for each rolling average duration, with the self-containment of shorter rolling average epochs within longer epochs also assessed (e.g. Do the 1 min peak running demands occur within the 10 min peak running demands). Peak TD and AveAcc demands occurred early in each half (median time = 7–17 min and 6–16 min, respectively). Conversely, peak HSD covered was uniformly distributed (Skewness = 0–0.5, Kurtosis = 1.7–2.0). There were low-moderate levels of self-containment for each peak match running period (10–51%), dependent upon metric. Peak match running demands for TD and AveAcc occurred at similar stages of a match where TD and acceleration volumes are typically greatest, whereas peak HSD demands appeared more unpredictable. These timings may help inform training prescriptions in preparation of athletes for competition.